Vascularization for Cooling and Reduced Thermal Stresses - Çetkin, Erdal; Çetkin, Erdal; Lorente, S.; Bejan, A. (Elsevier Ltd., 2015)
This paper documents the effect of thermal expansion on a vascularized plate that is heated and loaded mechanically. Vascular cooling channels embedded in a circular plate provide cooling and mechanical strength. The coolant enters the plate from the center and leaves after it cools the plate to an allowable temperature limit. The mechanical strength of the plate decreases because of the embedded cooling channels. However, cooling the plate under an allowable temperature level decreases the thermal stresses. The mechanical strength of the plate which is heated and loaded mechanically at the same time can be increased by inserting cooling channels in it. The mechanical and thermofluid behavior of a vascularized plate was simulated numerically. The cooling channel configurations that provide the smallest peak temperature and von Mises stress are documented. There is one cooling channel configuration that is the best for the given set of boundary conditions and constraints; however, there is no single configuration that is best for all conditions.
Keywords: Constructal; Cooling; Strength; Thermal expansion; Vascularization